ANALISIS SIFAT FISIKA DAN KIMIA TANAH PADA BEBERAPA PENGGUNAAN LAHAN DI DESA WAIRARA KECAMATAN MAHU KABUPATEN SUMBA TIMUR - Ndawalu, Amos; Killa, Yonce Melyanus (Fakultas Pertanian Universitas Mataram, 2024)
This study aims to analyze the physical and chemical properties of soil on agricultural land in Wairara Village, Mahu sub-district, East Sumba district. The research was conducted in January-March of 2024. The methods used in this study were survey method and laboratory sample analysis. Determination of sampling locations was carried out by purposive sampling method (determination of samples is done intentionally by looking at land use in the research location). Sampling was conducted at a depth of 0-20 cm and in 12 different locations with 4 different land uses (rainfed rice fields, gardens, fields and shrubs). Research variables include soil pH, organic matter, cation exchange capacity (CEC), soil texture, permeability, and porosity. The results showed that soil texture included sandy loam, sandy clay loam, sandy clay and sandy clay. Permeability is in the category of moderate, fast, rather fast and very fast. Porosity includes areas with very porous porosity. pH at the research site is neutral, slightly alkaline and alkaline, while the category is moderate to very high. CEC values vary from 2.39-41.92 m.e./100g with low to very high categories.